ANALISIS PEMANFAATAN LIMBAH ABU BONGGOL JAGUNG CAMPUR ABU SEKAM PADI TERHADAP KUAT TEKAN BETON MUTU K200 - Maulana, Arya Dwi; Syakirul Iman, Abdika Setiawan; Kristiawan, Agung; Permata Suwandi, Putri Anggi (Universitas PGRI Semarang, 2025)
Along with the development of science and technology, many studies have been carried out to implement environmentally friendly concrete innovations. One of them uses agricultural waste as a concrete mixture, in Sewaka Village, Pemalang District, Pemalang Regency, agricultural waste from corn cobs and rice husks. The purpose of this study is to utilize waste as an additive to cement for concrete mixtures in the quality of K200 concrete with mixed materials in the form of corn cob ash mix rice husk ash. This research was carried out by mixing design, by making a standard concrete sample with K200 quality as a control, then making a concrete sample with several variations of corn cob ash substitution mixtur mix rice husk ash 5%, 10%, 15% to the weight of cement. The specimen sample uses a cube mold (15cm x 15cm x 15cm). From the test results on the concrete of corn cob ash substitution mixture mixed rice husk ash with a percentage of 5%, 10%, 15% of the 7 days and 14 days of age experienced a decrease in the compressive strength of the K200 plan, from the test it was obtained that the average compressive strength value of 5% variation of 7 days old was 136.00 (kg/cm2) and the age of 14 days was 151.11 (kg/cm2), 10% variation at 7 days of age 169.71 (kg/cm2) and 14 days of age at 164.85 (kg/cm2), variation of 15% at 7 days of age 153.44 (kg/cm2) and 14 days of age at 115.91 (kg/cm2).